Kenya : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2009)
Like most Sub-Saharan African countries, Kenya's economic growth appears to have been primarily driven by factor accumulation. The Selected Issues paper and Statistical Appendix for Kenya examines economic developments and policies. During the last two decades, Kenya has been plagued by pervasive problems of internal conflicts, constitutional crises, and corruption scandals. The governance agenda focuses on several reforms, including upgrading the public budget and financial management systems, strengthening the anticorruption institutions, and improving the judicial framework.